ANALISIS PROBLEMATIKA GURU DALAM MENERAPKAN MODEL PEMBELAJARAN PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SDN JUNGANYAR 2 BANGKALAN - Cahya Wilda Syahningrum Harlambang; Dzofiroh, Amirotudz; Adzani Pertiwi, Aldila; Ilmi, Arifatul; Ar Rohman, Ikbar; Sudi Praktikno, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to discover the challenges faced by teachers in implementing the teaching model in the fourth grade of SDN Junganyar 2 Bangkalan, Indonesia. The research was conducted at SDN Junganyar 2 Socah, located in Bangkalan. This research is of a qualitative nature, utilizing data collection methods such as questionnaires, observations, interviews, and documentation. The findings of this study reveal facts related to issues arising from the use of inappropriate models and methods, which can lead to boredom, low concentration, and difficulty in speaking Indonesian. The data from the questionnaire indicates that 75% of students enjoy the Indonesian subject, while 90% struggle with maintaining concentration during their studies.